2019
DOI: 10.1186/s12932-019-0061-3
|View full text |Cite
|
Sign up to set email alerts
|

The formation of spinel-group minerals in contaminated soils: the sequestration of metal(loid)s by unexpected incidental nanoparticles

Abstract: Mineralogical studies of contaminated soils affected by smelter emission and dust from mining activities indicate that minerals of the spinel group are one of the common hosts of metal-bearing contaminants. Spinel group minerals typically originate from high temperature processes, but an increasing number of studies indicate that metal-bearing spinel group minerals can also form under ambient Earth surface conditions in surficial soils. In this contribution to honor Donald Sparks, we show that the spinels Zn-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…39 They are of great signicance in geological, environmental and materials sciences due to their physical properties and their ability to incorporate a variety of mono-, di-, tri-, tetraand pentavalent cations. 39 Spinel-type minerals such as magnetite also occur as NPs in the upper horizons of soils, where they form through various abiotic and biotic processes. 39 Cuprite is a common oxidation product of Cu-suldes and occurs in association with Cu-carbonates (azurite and malachite) and metallic Cu.…”
Section: Origin Of the Mineral Inclusions Observed In The Om Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…39 They are of great signicance in geological, environmental and materials sciences due to their physical properties and their ability to incorporate a variety of mono-, di-, tri-, tetraand pentavalent cations. 39 Spinel-type minerals such as magnetite also occur as NPs in the upper horizons of soils, where they form through various abiotic and biotic processes. 39 Cuprite is a common oxidation product of Cu-suldes and occurs in association with Cu-carbonates (azurite and malachite) and metallic Cu.…”
Section: Origin Of the Mineral Inclusions Observed In The Om Particlesmentioning
confidence: 99%
“…39 Spinel-type minerals such as magnetite also occur as NPs in the upper horizons of soils, where they form through various abiotic and biotic processes. 39 Cuprite is a common oxidation product of Cu-suldes and occurs in association with Cu-carbonates (azurite and malachite) and metallic Cu. 40 Illite is known to neo-form in soils through the weathering of rock forming minerals.…”
Section: Origin Of the Mineral Inclusions Observed In The Om Particlesmentioning
confidence: 99%
“…16,17 Moreover smelter emission and dust from the mining activities enrich soils with the magnetic spinel group minerals, one of the common hosts of metal-bearing contaminants including Pb. 18 Lascu et al reported that a qualitative estimate of the magnetic properties of the sediments can be evaluated from the χ measurements but requires the knowledge of magnetic particles grain size. 10 Therefore, the extent of surface modifications of magnetic NPs, biomolecular conformations, grain size, and the degree of magnetic dipolar interactions evolved from polydispersity may facilitate the growth of magnetic field-directed self-assembled nanostructures in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to microbes, nanoparticles (which are defined as clusters, crystals, and amorphous phases having at least one dimension of 1–100 nm, Caraballo et al ., 2015), have been found prevalent and abundant in a wide range of natural systems, from groundwater, soils, volcanic ashes, glaciers, thawing permafrost, to lacustrine, riverine, estuarine and marine settings (Hochella et al ., 2008; Gartman et al ., 2014; Johnson et al ., 2014; Tepe and Bau, 2014, 2015; Hirst et al ., 2017; Graca et al ., 2018; Hawkings et al ., 2018; Schindler et al ., 2019). In contrast to the consensus that microbial life is central to many geological and environmental processes on Earth, the integral role of nanoparticles in global biogeochemical cycles has only started to be recognized.…”
Section: Introductionmentioning
confidence: 99%